The Role of the Kamsel Unit Through Dikmas Traffic in Preventing Traffic Violations by Private Workers in the Legal Area of the Pasuruan Police - Putratama, Muhammad Rafly (Police Studies Review, 2024)
The high number of traffic violations in the Pasuruan Regency area is a matter that needs to be considered and handled by the Pasuruan Resort Police where this can hamper the activities of the Pasuruan Regency community such as congestion and can even result in traffic accidents. The main cause of the high number of traffic violations by motorized vehicle drivers is the lack of public awareness of traffic rules. Traffic Public Education is a preventive operational activity to increase public awareness in traffic so that the risk of traffic violation can be reduced. The implementation of Traffic Public Education is carried out in accordance with the Implementation Instructions of the National Police Chief No. Pol: Juklak/05/V/2003. As an analytical tool to discuss this research, George R Terry’s management theory and SWOT analysis theory are used with a qualitative approach. Data collection was performed through interview, observation and document review techniques. Meanwhile, data analysis was executed with data reduction, data presentation, and drawing conclusions.